Visualization as an information component of journals in the system of documentation communications - E. V. Martynova; L. M. Tujeva (Библиосфера)
The article reviews the means used for visualizing information in magazines. A tendency for a greater expressivity of magazine articles due to the development of the electronic visual culture is marked.